DINAMIKA RANTAI PASOK INDUSTRI PERIKANAN DI KAWASAN TAMAN NASIONAL SEBANGAU DAN IMPLIKASINYA TERHADAP KETAHANAN PANGAN REGIONAL - Suherman Suherman; Nurlia Eka Damayanti; Muhammad Farras Nasrida; Ulan Ulan; Dede Ardiansyah; Utari Yolla Sundari (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
This study presents an in-depth and comprehensive analysis of the structure, performance, and development strategy of the inland fishery supply chain in the buffer zone of Sebangau National Park (SNP), Central Kalimantan. As one of the world's largest and most crucial tropical peat swamp ecosystems, SNP plays a dual role as a biodiversity reservoir and a pillar of the local economy through the fishery sector. However, this vast potential faces a paradox of supply chain inefficiency, market information asymmetry, and vulnerability to extreme peat hydrological dynamics. This research adopts a sequential exploratory mixed-methods design, integrating the depth of qualitative data from in-depth interviews and participatory observation with the rigor of quantitative analysis through SWOT (Strengths, Weaknesses, Opportunities, Threats) and QSPM (Quantitative Strategic Planning Matrix) instruments. The results reveal a supply chain anatomy dominated by patron-client relationships, with fishermen positioned as price takers. Key findings indicate that the greatest internal strengths lie in the fishermen's social capital and Traditional Ecological Knowledge (TEK), as well as adaptive innovations in live fish storage. Conversely, the absence of cold chain infrastructure and downstreaming facilities represents a critical weakness causing economic value-added leakage. Through QSPM strategy simulation, this study establishes the downstreaming of fish-based food products as the main priority strategy with the highest Total Attractiveness Score (TAS) of 1.00, outperforming aquaculture and ecotourism strategies. This article provides a theoretical contribution to the literature on supply chain management in wetlands and offers practical policy recommendations for transformation toward adaptive and sustainable regional food security.